2001
DOI: 10.1017/s1481803500005327
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for a career in emergency medicine: a profile of the 1996 US applicant pool

Abstract: Introduction: Although some studies have tried to assess the factors leading to choice of specialty, none have been specific to emergency medicine (EM). With a doubling of the number of EM residency programs in the past decade, an assessment of the career motivations of residents is in order. Objectives: To identify and rank the factors that lead candidates to choose EM as a career. Methods: Fifty-four participating EM programs returned a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…EM is a specialty that comes with unique challenges and rewards for practitioners in the field. (3,6,7,15) EM specialists are expected to be quick at formulating accurate diagnoses with little information at hand, possess excellent dexterity for performing a wide range of procedures, and be comfortable with dealing with trauma and deaths on a daily basis. Hence, it comes as no surprise that internal factors such as 'personality fit' turned out to be more important than external factors, such as salary and working hours, in influencing one's decision to pursue EM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EM is a specialty that comes with unique challenges and rewards for practitioners in the field. (3,6,7,15) EM specialists are expected to be quick at formulating accurate diagnoses with little information at hand, possess excellent dexterity for performing a wide range of procedures, and be comfortable with dealing with trauma and deaths on a daily basis. Hence, it comes as no surprise that internal factors such as 'personality fit' turned out to be more important than external factors, such as salary and working hours, in influencing one's decision to pursue EM.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12) We then collected feedback on the questionnaire from a group of National University Health System EM residents on whether the instructions and questions were clear, whether the length of the questionnaire was appropriate, and whether there were questions that they objected to answering. The final version of the questionnaire, which was revised based on the feedback of EM residents from the pilot study, contained 35 items.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Previous studies have revealed that variety in clinical pathology, emphasis on acute care, previous work in an emergency setting, and fl exibility both in terms of practice location and work schedule are the main factors in EPs' career selection. [2] Career longevity, job satisfaction, and burnout among EPs are areas of debate. [3,4] Recent studies have reported various problems in the fi eld of emergency medicine, especially in relation to night shifts, emergency department (ED) overcrowding, limited resources, job stresses, litigation concerns, and miscommunication between patients and physicians.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there was no objective measure of lifestyle friendliness or work-related quality of life used in these trials. In other publications, EM is described as a very attractive specialty among medical students, 7 largely because of clinical factors (e.g., diversity of clinical pathology and emphasis on acute care) and because it allows for a controllable lifestyle. 8,9 EM is considered a lifestyle specialty 8,9 with predictable hours and a balance among clinical work, administrative duties, organizational commitments, teaching, and/or research.…”
Section: Discussionmentioning
confidence: 99%